Small Business Development Centers and Rural Entrepreneurial Development Strategies: Are We Doing Enough for Rural America? (Journal of Small Business Strategy (archive only), 2021)
Many states across the United States have significant rural populations, which typically face different sets of challenges than those closer to urban populations. This is particularly evident in the different types of opportunities that small businesses face in those rural areas. In recent years, various efforts - both at a national and local level - have been taken to increase those opportunities for rural small businesses. However, those efforts have not always produced the results that are envisioned. Utilizing information about Small Business Development Center (SBDC) strategies to serve small businesses in both rural and urban areas, we highlight the efforts that work to aid rural entrepreneurs as well as those that fall short.